2023
DOI: 10.1182/blood.2022016620
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea for secondary stroke prevention in children with sickle cell anemia in Nigeria: a randomized controlled trial

Abstract: We tested the hypothesis that fixed oral moderate-dose hydroxyurea (20 mg/kg/day) for initial treatment of secondary stroke prevention results in an 80% relative risk reduction of stroke or death when compared to fixed oral low-dose hydroxyurea (10 mg/kg/day) in a phase III, double-blind, parallel-group, randomized controlled trial in children with sickle cell anemia (SCA) living in Nigeria. The median participant follow-up was 1.6 years (interquartile range 1.0-2.3) with a planned minimum follow-up of 3.0 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Again, similar to the SPIN trial, no participant stopped treatment for myelosuppression in either group despite monthly laboratory monitoring for a minimum follow‐up of 3 years, further supporting the limited need for frequent laboratory monitoring with either low or moderate hydroxyurea dosing strategies. In a similar study design investigating the role of hydroxyurea for secondary stroke prevention, the phase III SPRINT trial found similar efficacy in secondary stroke prevention for fixed low‐dose hydroxyurea (10 mg/kg/day) compared to fixed moderate dose (20 mg/kg/day) in 101 Nigerian children with SCA who had previously suffered a stroke 26 . As a direct outcome of these studies, three states in Nigeria (Kano, Kaduna, Katsina) have acted to ensure government purchase of hydroxyurea to support local stroke prevention programming 54 .…”
Section: Hydroxyurea In Sub‐saharan Africa: Evidence From Recent Studiesmentioning
confidence: 96%
See 3 more Smart Citations
“…Again, similar to the SPIN trial, no participant stopped treatment for myelosuppression in either group despite monthly laboratory monitoring for a minimum follow‐up of 3 years, further supporting the limited need for frequent laboratory monitoring with either low or moderate hydroxyurea dosing strategies. In a similar study design investigating the role of hydroxyurea for secondary stroke prevention, the phase III SPRINT trial found similar efficacy in secondary stroke prevention for fixed low‐dose hydroxyurea (10 mg/kg/day) compared to fixed moderate dose (20 mg/kg/day) in 101 Nigerian children with SCA who had previously suffered a stroke 26 . As a direct outcome of these studies, three states in Nigeria (Kano, Kaduna, Katsina) have acted to ensure government purchase of hydroxyurea to support local stroke prevention programming 54 .…”
Section: Hydroxyurea In Sub‐saharan Africa: Evidence From Recent Studiesmentioning
confidence: 96%
“…If health care providers cannot perform a CBC, there is the belief that hydroxyurea cannot be administered at all due to safety concerns. We have seen from the studies discussed above that hematologic toxicity is rare (<5% of CBCs with hematologic toxicity) and often not associated with any clinical signs or symptoms 26,27,31,49,50 . The requirement for laboratory monitoring is still not clear, but it appears quite safe to perform laboratory monitoring only every 3–6 months, though there is a question as to whether that is even necessary.…”
Section: Hydroxyurea In Sub‐saharan Africa: Challenges and Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all patients with sickle cell and stroke have arteriopathy and, consequently, providers should perform a complete stroke workup to look for other factors that may increase the risk of stroke in these children and young adults [55]. Although chronic transfusion therapy remains an important preventive strategy for children with sickle cell and stroke or with arteriopathy, hydroxyurea is a reasonable lower cost alternative [11]. There are ongoing gene therapy trials for sickle cell disease with initially promising results in eliminating vaso-occlusive crises, though further research is needed to determine optimum timing and how this influences stroke risk [74,75 ▪ ].…”
Section: Specific Considerations By Stroke Etiologymentioning
confidence: 99%